Simultaneous detection of the spike and nucleocapsid proteins from SARS-CoV-2 based on ultrasensitive single molecule assays - Cai, Qiyong (Anal Bioanal Chem, 2021)
Nucleic acid detection technology based on polymerase chain reaction (PCR) and antibody detection based on immunochromatography still have many problems such as false negatives for the diagnosis of coronavirus disease 2019 (COVID-19). Therefore, it is of great importance to develop new techniques to improve the diagnostic accuracy of COVID-19. We herein developed an ultrasensitive, rapid, and duplex digital enzyme-linked immunosorbent assay (dELISA) for simultaneous detection of spike (S-RBD) and nucleocapsid (N) proteins of SARS-CoV-2 based on a single molecule array. This assay effectively combines magnetic bead encoding technology and the ultrasensitive detection capability of a single molecule array. The detection strategies of S-RBD protein and N-protein exhibited wide response ranges of 0.34–1065 pg/mL and 0.183–338 pg/mL with detection limits of 20.6 fg/mL and 69.8 fg/mL, respectively. It is a highly specific method for the simultaneous detection of S-RBD protein and N-protein and has minimal interference from other blood proteins. Moreover, the spike assay showed a satisfactory and reproducible recovery rate for the detection of S-RBD protein and N-protein in serum samples. Overall, this work provides a highly sensitive method for the simultaneous detection of S-RBD protein and N-protein, which shows ultrasensitivity and high signal-to-noise ratio and contributes to improve the diagnosis accuracy of COVID-19. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00216-021-03435-z.